Cognitive processes in problem-solving across biogeochemical cycles: A comparative study of carbon, water, and nitrogen cycles - Anggia Fitri Damayanti; Adi Rahmat; Yanti Hamdiyati; Amprasto Amprasto; Muhamad Wafda Jamil (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
Biogeochemical cycle is one of the topics in biology learning that can train students' problem-solving ability. This study aims to analyze and compare the cognitive processes in students' problem-solving ability on carbon cycle, water cycle, and nitrogen cycle topics. 32 high school students were assessed using a descriptive method with problem-solving test based on Marzano & Kendall’s indicators, which emphasize how cognitive processes function in solving problems. Data were analyzed using Kruskal-Wallis statistical test, followed by grouping students into problem-solving ability categories. Based on the number of students in each category of problem-solving ability, students have better problem-solving ability in nitrogen cycle compared to carbon cycle and water cycle. The difference in the distribution of problem-solving abilities of three biogeochemical cycles shows that students' cognitive processes vary for each cycle. This study highlights the importance of integrating the three biogeochemical cycles in learning to develop problem-solving ability comprehensively. The findings also suggest that students’ cognitive processes in problem-solving may be supported by their mastery of concepts and experience relevant to the problem.Abstrak. Daur biogeokimia merupakan salah satu topik dalam pembelajaran biologi yang dapat melatih kemampuan problem solving siswa. Penelitian ini bertujuan untuk menganalisis dan membandingkan proses kognitif dalam kemampuan problem solving siswa pada materi daur karbon, daur air, dan daur nitrogen. Sebanyak 32 siswa SMA diuji menggunakan metode deskriptif dengan tes problem solving berdasarkan indikator Marzano & Kendall, yang menekankan bagaimana proses kognitif bekerja dalam memecahkan masalah. Data penelitian dianalisis dengan uji statistik Kruskal-Wallis, diikuti dengan pengelompokan siswa ke dalam kategori kemampuan problem solving. Berdasarkan jumlah siswa pada setiap kategori kemampuan problem-solving, siswa memiliki kemampuan problem-solving yang lebih baik pada materi daur nitrogen dibandingkan daur karbon dan daur air. Perbedaan distribusi kemampuan problem-solving ketiga daur biogeokimia menunjukkan bahwa proses kognitif berbeda-beda pada setiap daur. Penelitian ini menyoroti pentingnya integrasi ketiga daur biogeokimia dalam pembelajaran untuk melatihkan kemampuan problem-solving secara utuh. Temuan penelitian juga menemukan bahwa proses kognitif dalam problem-solving kemungkinan didukung oleh penguasaan konsep dan pengalaman yang relevan dengan masalah.